Genomic Diversity and Potential Transmission and Persistence of Salmonella in the Cambodian Vegetable Supply Chain - Abimel Salazar; Navin Sreng; Chanthol Peng; Yehzi Fu; Erin M. Nawrocki; Taejung Chung; Jessie Vipham; Edward G. Dudley; Jasna Kovac (Journal of Food Protection)
S. enterica isolates (n = 78) obtained from the vegetable supply chain (farms, distribution centers, markets) in two Cambodian provinces (Siem Reap, Battambang) were sequenced and analyzed. In silico identification of serotypes and detection of antimicrobial resistance genes was performed using SISTR and ABRicate, respectively. Isolates’ relatedness was assessed based on high-quality single nucleotide polymorphisms (hqSNPs) identified within each serotype using the CFSAN SNP pipeline. Among 29 detected serotypes, Paratyphi B var. Java was most abundant (n = 14), followed by Hvittingfoss (n = 11) and Thompson (n = 7). Paratyphi B var. Java was mostly found in farms (n = 5) and markets (n = 6), Hvittingfoss within distribution centers (n = 8), and Thompson at markets (n = 4) and farms (n = 3). Among Paratyphi B var. Java isolates, one phylogenetic clade contained four closely related isolates (0–1 SNP difference), collected at markets in different provinces on different days. Another clade contained two isolates that differed by one SNP, one obtained from a Battambang farm and one from a Siem Reap distribution center, suggesting a broad spread of Paratyphi B var. Java in the Cambodian vegetable supply chain. Hvittingfoss isolates clustered in two clades; one contained five identical isolates, four of which were obtained in different months from the distribution center and a farm in Battambang, suggesting possible transmission among supply chain stages. The second clade contained three isolates from the Battambang distribution center that differed by 0–1 SNP and were isolated in October and November, indicating possible persistence. Lastly, among 78 analyzed isolates, 14 carried antimicrobial resistance genes and seven out of these 14 carried genes with predicted resistance to more than three classes of antibiotics. Overall, highly similar isolates of Salmonella were identified over time and at different supply chain stages, suggesting possible persistence and transmission of Salmonella within and between supply chain stages.